The microarchitecture and chemical composition of the femur neck of senescent female rats after different physical training protocols - dos Santos Silva, Rafael Augusto [UNESP] (2024)
A sedentary lifestyle, coupled with a decrease in estrogen, impairs bone homeostasis, favoring to the development of osteopenia and osteoporosis, both recognized as risk factors for fractures. Here, we investigated the quality of the femur, particularly the femur neck region, and the ambulation performance of senescent rats subjected to three different physical training protocols during the periestropause period. Forty-eight female rats, 18 months of age, were subjected to a 120-day training period, three times a week. The rats were distributed into four groups: aerobic training (AT), strength training (ST), concurrent training (CT), or no training (NT). After the experimental period, at 21 months of age, ambulation performance and femur were analyzed using microtomography, Raman stereology, densitometry, and mechanical strength tests. The results demonstrated greater remodeling activity and improvement in resistance and bone microarchitecture in the femur neck of senescent female rats after undergoing physical training. Our verified higher intensities of bands related to collagen, phosphate, amide III, and amide I. Furthermore, the analysis of the secondary collagen structures indicated alterations in the collagen network due to the exercise, resulting in increased bone strength. Both AT and strength-based training proved beneficial, with AT showing greater adaptations in bone density and stiffness in the femur, while strength-based training greater adaptations in trabecular and cortical structure. These insights contribute to the understanding of the potential interventions for preventing osteopenia and osteoporosis, which are critical risk factors for fractures.